Entrepreneurial Team Diversity and Productivity: The Role of Family Relationships in Nascent Ventures. (March 2021) - Ko, Eun-Jeong; Wiklund, Johan; Pollack, Jeffrey M.
In this study, we examine how team diversity contributes to team productivity in nascent ventures depending on family relations. Specifically, we explore how bio-demographic diversity influences team productivity using data from a panel of 285 nascent venture teams over 5 years. Results suggest that age and gender diversity have negative impacts on team productivity, but that family relationships positively moderate these effects. To explain the phenomena, we relied on social identity theory and the discussion of the identity confirmation process. Through this novel theoretical framework, we describe how identity confirmation, through identification with a collective (i.e., family), and cross-categorization of family roles mitigate the negative impact of bio-demographic diversity. Our findings provide valuable insights to scholars interested in bio-demographic team diversity, family relationships, and the new venture creation process.